Efektifitas Pelatihan Self Leadership Untuk Meningkatkan Perilaku Inovatif Karyawan JMC IT Consultant Yogyakarta - Muflih Dahlan; Alimatus Sahrah (LPPM Universitas Proklamasi 45, 2023)
ABSTRACTInnovative behavior is driven by self-leadership, because employees can direct themselves to create ideas and solutions for their job. This study aims to determine the effectiveness of self-leadership training to improve employee innovative behavior. The subjects of this study were 10 employees who had innovative behavior in the medium and low categories. The research design used in this study was one group pretest-posttest design. The result show that in the paired sample t-test, t value was -8,533 (p < 0.05). Based on the results of research conducted, we can conclude self-leadership training can increase employee innovation. It is hoped that the company can use self-leadership training as an alternative to increase innovative behavior. In addition, further researchers are expected to involve the control group in order to make sure the effect of this treatment and can use another treatments to increase innovative behavior.